Origin of peralkaline granites of the Jurassic Bokan Mountain complex (southeastern Alaska) hosting rare metal mineralization. Issue 1 (2nd January 2016) - Dostal, Jaroslav; Shellnutt, J. Gregory
Abstract: The Jurassic Bokan Mountain complex (BMC), composed of arfvedsonite and/or aegirine-bearing peralkaline A-type granitic rocks, is a circular body about 3 km in diameter located in southeastern Alaska. Like many other highly fractionated granitic bodies, the BMC granites were affected by late magmatic or post-magmatic processes, which, however, did not modify the contents of major elements. The granitic rocks are distinctly enriched in high-field-strength elements (HFSEs), rare earth elements (REEs), Y, Th, and U but depleted in Ba, Sr, and Eu and have high positive ɛ Nd(T) values. Unlike the variations in the major elements, Sr and Ba, which can be accounted by fractional crystallization, the abundance of REE, Y, HFSE, U, and Th (the elements which are hosted in accessory phases) were modified by F-rich hydrothermal fluids. The BMC hosts significant rare metal mineralization related to the late-stage crystallization history of the complex involving late magmatic and/or post-magmatic fluids. The mineralization includes two types: (1) a U–Th deposit which was exploited at the former Ross-Adams mine and (2) REE and Y mineralization mostly hosted in felsic dikes. Thermodynamic modelling of granites and spatially associated mafic rocks using the programme Rhyolite-MELTS implies that the granites can be derived from the mafic rocks by fractional crystallization. It is suggested that such a process (i.e. derivation of peralkaline granitic magma from the alkali or transitional basaltic magmas derived by partial melting from a lithospheric source metasomatically enriched in rare metals) can be invoked for other peralkaline granitic rocks hosting rare metal deposits.